2000
DOI: 10.1088/0953-8984/12/30/310
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen storage in Pd clusters

Abstract: Hydrogen storage in a Pd cluster is studied theoretically using a self-consistent densityfunctional scheme with a norm-conserving pseudopotential. We mainly focus on the cuboctahedral Pd 13 H n clusters with n = 1, 6, 8, and 14. Two stable sites for hydrogen adsorption are found; one is slightly inside the square face of the cluster and the other is outside of the triangular face. Electronic states relevant to hydrogen adsorption are well described by the cluster-centre electronic states (CCSs); this term refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 25 publications
(23 reference statements)
0
50
0
Order By: Relevance
“…[7][8][9][10] Fe-H interaction at nanoscale is not an exception. Whetten et al suggests that gas phase small Fe clusters could form chemical bonds with H. 11 FeH molecules were detected by the near-infrared spectrum and the blue-green solar spectrum.…”
Section: Chemisorption Of Hydrogen On Fe Clusters Through Hybrid Bondmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10] Fe-H interaction at nanoscale is not an exception. Whetten et al suggests that gas phase small Fe clusters could form chemical bonds with H. 11 FeH molecules were detected by the near-infrared spectrum and the blue-green solar spectrum.…”
Section: Chemisorption Of Hydrogen On Fe Clusters Through Hybrid Bondmentioning
confidence: 99%
“…Hydrogenated Fe 1 has symmetrical configuration as can be seen in Figure 1. Additionally, the structure of hydrogenated Fe 1 forms 2-dimensional configurations until Fe 1 H 6 , where a 3-dimensional configuration then starts to form from FeH 7 .…”
Section: Chemisorption Of Hydrogen On Fe Clusters Through Hybrid Bondmentioning
confidence: 99%
“…It is found that the behavior and electronic structure of H in clusters are similar to those in a crystal [15][16][17][18]. Besides quite a few reports about alloying effects on different systems by using the cluster model [19][20][21][22][23][24][25], Yang et al [26] recently employed a cluster model to study the transition metal alloying effect on the chemical bonding in TiH 2 .…”
Section: Introductionmentioning
confidence: 93%
“…Recently, research has been focused on palladium (Pd) nanoclusters because of possible applications in the fields of hydrogen storage [1,2], hydrogen detection [3], and catalysts [4,5]. Therefore, intensive research is required to develop nanocluster sources to produce more intensive nanocluster beam, and to provide further control of nanocluster size distributions [6,7].…”
Section: Introductionmentioning
confidence: 99%